Congenital fibrosis of superior rectus and superior oblique: a case report. Issue 1 (January 1985) - Prakash, P; Menon, V; Ghosh, G
Abstract : A rare case of possible postinflammatory fibrosis of the superior rectus and superior oblique muscles, resulting in marked hypotropia with pseudoptosis, is described, together with the surgical management.